اشتراط الصيانة على المستأجر في تطبيقات المصارف الإسلامية بماليزيا : دراسة فقهية تقويمية - Sham Irzatul Mohd Nazri (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Islamic hire purchase has become a popular contemporary Islamic contract which is applied mostly in Islamic banks in Malaysia to finance the purchase of cars. In the practice of this contract, scholars are having an on-going debate on the issue of stipulating maintenance (siyanah) on the lessee; a critical Shari'ah issue. It is even criticized that the operation of Islamic hire purchase is quite similar to the practice of interest-based conventional banking yet contrary to Islamic law (fiqh). Therefore, this study aims at discussing the view of Islamic jurisprudence on this issue. It has discovered that the actual practice for the maintenance of the leased asset in Islamic banks in Malaysia is to learn the extent of its acceptance or violation in Islamic jurisprudence. The study has adopted inductive method to collect data through studying classical and modern sources of Islamic jurisprudence in economics and law. Besides, it employed field studies through interviews and personal contacts with the staff of Islamic banks. After that, the study used analytical and evaluative approaches to analyze the opinions of the classical and contemporary Islamic jurists as well as to examine the operations of Islamic banks. Among the most important findings of this study is that Islamic jurisprudence permits banks to stipulate the operational maintenance on the lessee as it is originally binding on him. On the other hand, the maintenance necessary to enable the lessee to get benefit from the leased asset is in fact compulsory on the lessor. This type of maintenance is not allowed to be stipulated on the customers due to uncertainty, and based on the legal maxim, “profit comes with liability”.